'A dialogue between the real-world and the operational model' – The realities of design in Bruce Archer's 1968 doctoral thesis. (May 2018) - Boyd Davis, Stephen; Gristwood, Simone
Abstract : The article centres on a single document, the 1968 doctoral thesis of L. Bruce Archer. It traces Archer's earlier publications and the sources that informed and inspired his thinking as a way of understanding his influential work at the Royal College of Art from 1962. Analysis suggests that Archer's ambition for a rigorous 'science of design' inspired by linear algorithmic approaches was increasingly threatened with disruption by his experience of large, complex design projects. Reflecting on Archer's engagement with other models of designing, the article ends with Archer's retrospective view and an account of his significantly altered opinions. Archer is located as both a theorist and someone fascinated by the commercial and practical aspects of designing. Highlights: Demonstrates the significant changes in L. Bruce Archer's models of design. Probes the theoretical and practical influences on his work and others'. Identifies a general shift from linear to more complex models of designing.